Dampak Enso pada Faktor Hujan di Indonesia - Bayong Tjasyono HK; Bannu Bannu (Jurnal Matematika & Sains, 2003)
The Indonesian region is characterized by the activity of tropospheric convection. In the ENSO (El NiÃ±o âSouthern Oscillation) event, the convective clouds displace to the eastern Pacific ocean due to the weakened trade winds. The ENSO phenomenon is the biggest player in the game of annual climate variation, while monsoon plays a role in the seasonal variations. The ENSO also brings about serious climate disaster in global area, for instance in the drought Indonesia, in the food Ecuador and so on. The influence of ENSO events is profoundley felt in some parts of the Indonesian region, i.e., the number of rainfall less than that in the pre and post ENSO years. The ENSO event also causes long dry season in the several parts of the Indonesian region, it means that rice planting will be very late. The isolines of rain factor of the value less than 5 covered a greater area in the ENSO year than that in the non ENSO years.